Estimating the return times of great Himalayan earthquakes in eastern Nepal: Evidence from the Patu and Bardibas strands of the Main Frontal Thrust. Issue 9 (15th September 2014) - Bollinger, L.; Sapkota, S. N.; Tapponnier, P.; Klinger, Y.; Rizza, M.; Van der Woerd, J.; Tiwari, D. R.; Pandey, R.; Bitri, A.; Bes de Berc, S.
Abstract The return times of large Himalayan earthquakes are poorly constrained. Despite historical devastation of cities along the mountain range, definitive links between events and specific segments of the Main Frontal Thrust (MFT) are not established, and paleoseismological records have not documented the occurrence of several similar events at the same location. In east central Nepal, however, recently discovered primary surface ruptures of that megathrust in the A.D. 1255 and 1934 earthquakes are associated with flights of tectonically uplifted terraces. We present here a refined, longer slip history of the MFT's two overlapping strands (Patu and Bardibas Thrusts) in that region, based on updated geomorphic/neotectonic mapping of active faulting, two 1.3 km long shallow seismic profiles, and logging of two river‐cut cliffs, three paleoseismological trenches, and several pits, with constraints from 74 detrital charcoals and 14 cosmogenic nuclide ages. The amount of hanging wall uplift on the Patu thrust since 3650 ± 450 years requires three more events than the two aforementioned. The uplift rate (8.5 ± 1.5 mm/yr), thrust dip (25° ± 5°N), and apparent characteristic behavior imply 12–17.5 m of slip per event. On the Bardibas thrust, discrete pulses of colluvial deposition resulting from the coseismic growth of a flexural fold scarp suggest the occurrence of six or seven paleo‐earthquakes in the last 4500 ± 50 years. The coeval rupture of both strands during great Himalayan earthquakes implies that in eastern Nepal, the late Holocene return times of such earthquakes probably ranged between 750 ± 140 and 870 ± 350 years.